(untitled) (Comprehensive Journal of Science, 2025)
his paper examines the fundamental relationship between linear algebra and artificial intelligence techniques, as linear algebra represents the fundamental framework upon which many machine learning algorithms are based. By analyzing mathematical concepts such as matrices, vectors, eigenvalues, and singular value decomposition (SVD), we highlight how these concepts can be harnessed to improve the performance of intelligent models and develop effective techniques for data analysis, classification, and prediction. We also present applied experiments that demonstrate the practical use of linear algebra in modern artificial intelligence models